Optimization of fermentation technology of traditional highland barley wine based on fuzzy mathematical sensory evaluation and response surface method - ZHANG Chen, YAN Yingying, ZHANG Wenhui (Zhongguo niangzao)
A traditional highland barley wine was prepared with highland barley as raw material and Jiuqu as saccharifying starter. With alcohol content and sensory score as evaluation indexes, the fermentation process conditions of the wine were optimized by fuzzy sensory evaluation and response surface method, and the physicochemical indexes were analyzed. The results showed that the optimal fermentation process of the wine was Jiuqu addition 3.6‰, fermentation temperature 28 ℃ and time 2 d, the solid-liquid ratio 1∶2 (g∶ml). Under these optimal conditions, the alcohol content of the highland barley wine was 6.50%vol, the sensory score was 93.16. The wine body was slightly yellow and bright, and the wine aroma was prominent, sweet and refreshing, mellow and delicate. The acidity, total sugar, non-sugar solid substance and amino acid nitrogen of the wine were 3.42 g/L, 5.50 g/L, 14.66 g/L and 0.17 g/L, respectively.